Assessing environmental impacts and change in Myanmar's mangrove ecosystem service value due to deforestation (2000–2014) - Ronald C. Estoque; Soe W. Myint; Chuyuan Wang; Asif Ishtiaque; Toe T. Aung; Lucy Emerton; Makoto Ooba; Yasuaki Hijioka; Myat S. Mon; Zhe Wang; Chao Fan (Global Change Biology, 2018)
Myanmar is one of the mangrove‐richest countries in the world, providing valuable ecosystem services to people. However, due to deforestation driven primarily by agricultural expansion, Myanmar's mangrove forest cover has declined dramatically over the past few decades, while what remains is still under pressure. To support management planning, accurate quantification of mangrove forest cover changes on a national scale is needed. In this study, we quantified Myanmar's mangrove forest cover changes between 2000 and 2014 using remotely sensed data, examined the environmental impacts of such changes, and estimated the changes in the economic values of mangrove ecosystem services in the country. Results indicate that Myanmar had a net mangrove loss of 191,122 ha over the study period. Since 2000, Myanmar has been losing mangrove forest cover at an alarming rate of 14,619 ha/year (2.2%/year). The loss was predominant in Rakhine and Ayeyarwady. The observed mangrove forest cover loss has resulted in decreased evapotranspiration, carbon stock, and tree cover percentage. Due to deforestation, Myanmar also suffered a net loss of 2,397 million US $/year in its mangrove ecosystem service value (i.e. 28.7% decrease from 2000), in which maintenance of fisheries nursery populations and habitat and coastal protection were among those services that were greatly affected. We suggest that intensive reforestation and mangrove protection programs be implemented immediately. Agroforestry and community forestry programs are encouraged in areas that are under immense pressure from paddy field expansion, fuelwood extraction, charcoal production, and fish and shrimp farming activities. Potential alternative sustainable solutions should include intensive government‐led private forest plantations or community‐owned forest plantations to be developed with care by local farmers, nongovernmental organizations, and business owners.

Functional redundancy of multiple forest taxa along an elevational gradient: predicting the consequences of non‐random species loss - Akira S. Mori; Takayuki Shiono; Takashi F. Haraguchi; Aino T. Ota; Dai Koide; Takayuki Ohgue; Ryo Kitagawa; Ryo Maeshiro; Toe Toe Aung; Taizo Nakamori; Yusuke Hagiwara; Shunsuke Matsuoka; et al. (Journal of Biogeography, 2015)
Aims Climate change can substantially alter ecological communities. However, we hypothesized that, even if novel communities emerge, those communities may not be novel in terms of functional composition. To infer the processes associated with rising temperatures, we evaluated elevational taxonomic/functional turnover of plant and invertebrate communities. Because climate change interacts synergistically with other environmental factors, and therefore is not the sole driver of change in ecological communities, we also considered how the taxonomic/functional composition of the communities would be affected by mammalian overgrazing/browsing, which has become prominent in the study region. Location Shiretoko National Park, Shiretoko Peninsular, Hokkaido, Japan. Methods We investigated the diversity of eight groups of organisms (taxa) in forests of northern Japan, and calculated the distance decay of taxonomic/functional similarity (Sørensen's β‐diversity) along an elevational gradient. A null model was used to separate functional turnover from taxonomic turnover. We then simulated how taxonomic/functional turnover along the gradient would be changed after non‐random loss of species sensitive to mammalian herbivory. Results We found that each group showed elevational decay in taxonomic similarity. Along an elevational gradient, species groups structured by stronger dispersal limitation showed faster species turnover. This suggested differences in the process of climate‐induced species reassembly among the groups. We also found that elevational turnover of communities based on functional traits tended to be lower than that based on taxonomic identity for the majority of the groups, supporting our hypothesis of functional redundancy across the elevational gradient. We thus speculated that climate‐induced emergence of taxonomically novel communities may have limited influence on critical ecosystem processes supported by functional diversity. Furthermore, while random species loss did not change functional turnover, non‐random loss of species attributable to mammalian herbivory substantially accelerated elevational functional turnover of the taxa. This suggested a possible loss of the functional redundancy of communities. Main conclusions Future communities may be novel not simply because climates are changing at unprecedented rates but also because of the synergetic influences of other environmental changes. Thus ecological processes may be more seriously affected in the future than is generally anticipated based on existing climate‐change scenarios, with possible consequences for ecosystem functioning.